EBV-EBNA1 constructs an immunosuppressive microenvironment for nasopharyngeal carcinoma by promoting the chemoattraction of Treg cells - Lu Wang; Fan Wang; Jie Wang; Rui Deng; Shaofen Huo; Yunfan Luo; Xiong Liu; Bao Zhang; Juan Lu; Xiangping Li (Journal for ImmunoTherapy of Cancer)
Background Nasopharyngeal carcinoma (NPC) is primarily caused by the Epstein-Barr virus (EBV) infection in NPC endemic areas. EBNA1 is an EBV-encoded nuclear antigen, which plays a critical role in the maintenance and replication of EBV genome. However, the mechanisms of EBNA1-promoted NPC immune escape are unknown. Regulatory T (Treg) cells are among the key regulators in restraining antitumor responses. However, the mechanisms of accumulation of Treg cells in NPC have not been defined. This study attempted to identify the detailed mechanisms of EBNA1 functions as a tumor accelerator to promote NPC immune escape by enhancing chemoattraction of Treg cells.Methods mRNA profiles were determined by next-generation sequencing in NPC cells. In vitro and in vivo assays were performed to analyze the role of EBNA1 in regulation of recruitment of Treg cells. Colocation and coimmunoprecipitation analyzes were used to identify the SMAD3/c-JUN complex. Chromatin immunoprecipitation assay and dual luciferase reporter assays were designed to demonstrate c-JUN binding to miR-200a promoter and miR-200a targeting to CXCL12 3’Untranslated Regions. The hepatocellular carcinoma models were designed to demonstrate universality of the CXCL12-CXCR4-Treg axis in promoting immune evasion of various tumors.Result A novel molecular mechanism was identified that involves EBV-EBNA1-stimulated chemotactic migration of Treg cells toward NPC microenvironment by upregulation of the transforming growth factor-β1 (TGFβ1)-SMAD3-PI3K-AKT-c-JUN-CXCL12-CXCR4 axis and downregulation of miR-200a. EBV-EBNA1 promotes the chemoattraction of Treg cells by governing the protein–protein interactions of the SMAD3/c-JUN complex in a TGFβ1-dependent manner in vitro and in vivo. TGFβ1 suppresses miR-200a by enhancing the SMAD3/c-JUN complex. miR-200a negatively regulates the CXCL12 chemokine by direct targeting of the CXCL12 3’UTR region. However, CXCL12 acts as the target gene of miR-200a and as an inhibitor of miR-200a transcription, and inhibition of miR-200a by CXCL12 is mediated by c-JUN, which directly binds to the miR-200a promoter and forms a c-JUN-miR-200a-CXCL12-c-JUN feedback loop. In addition, enhanced CXCL12 efficiently attracts CXCR4-positive Treg cells to remodel an immunosuppressive microenvironment.Conclusions EBV-EBNA1 promotes chemotactic migration of Treg cells via the TGFβ1-SMAD3-PI3K-AKT-c-JUN-miR-200a-CXCL12-CXCR4 axis in the NPC microenvironment. These results suggest that EBV-EBNA1 may serve as a potential therapeutic target to reshape the NPC microenvironment.